Komunikasi Interpersonal Pemimpin Redaksi Radar Mojokerto dalam Manajemen Krisis Media Online - Ummi Kulsum; Nelly Fitri Dwiyanti; Fitri Adelia Pratiwi; Dina Kurniawati; Muhammad Syaiful Rizal (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to reveal the role of interpersonal communication by the editor-in-chief in crisis management within the online media outlet Radar Mojokerto. In the midst of the fast-paced digital information flow and increasing public scrutiny, local media are expected not only to deliver news quickly but also accurately and responsibly. This research adopts a descriptive qualitative approach using in-depth interviews, participatory observation, and documentation techniques. The findings show that the editor-in-chief plays a central role in maintaining newsroom stability through strategic interpersonal communication, including direct guidance in editorial meetings, mentoring for junior journalists, and utilizing digital data to address content shortages. Interpersonal communication effectively accelerates decision-making, sustains team motivation, and minimizes misunderstandings under pressure. With a solution-oriented and responsive leadership approach, the editor-in-chief is able to uphold the media's credibility while fostering a supportive work environment. These findings offer practical contributions for local media in developing effective communication strategies to manage crises in the digital era.